THE BORDA METHOD FOR SCORING PARKING OFFICER PERFORMANCE AT DEPARTEMENT OF TRANSPORTATION ASAHAN - Firdha Agis Utami Batu Bara; Muhammad Ardiansyah Sembiring; Chitra Latiffani (STMIK Royal, 2023)
Abstract: Determination of the best performance of parking attendants at the Asahan District Transportation Service aims to increase responsibility and high loyalty to get satisfactory performance results and award parking attendants with the best performance. The assessment of the best performance of parking officers was carried out by 3 assessors namely traffic engineering management, parking section, parking administration staff. The problem in assessing the best performance of parking attendants is that there is no structured system so that the assessment time is quite long, around 2-3 weeks. In addition, the assessment still tends to be subjective, for example the parking attendant's assessment is based on closeness and kinship, causing jealousy. Overcoming this requires a computer system that helps decision making, namely a decision support system for determining the best performance of parking attendants at the Asahan District Transportation Service in this study using the BORDA method. The borda method is used to combine the results of the decision assessment of each appraiser so that the final result is the best performance of the parking attendant. The purpose of this research is to create a computerized system that will later assist in determining the best performance appraisal of parking attendants every year. Based on the research results of the system for determining the best performance of parking attendants in the form of ranking the final score of each parking attendant. The highest value is used as the best performance suggestion for parking attendants. Keywords: borda method; decision support system; parking attendant performance Abstrak: Penentuan kinerja terbaik petugas parkir pada Dinas Perhubungan Kabupaten Asahan bertujuan untuk perlu meningkatkan tanggung jawab dan loyalitas yang tinggi mendapatkan hasil kinerja yang memuaskan dan pemberian perhargaan bagi petugas parkir memiliki kinerja terbaik. Penilaian kinerja terbaik petugas parkir dilakukan oleh 3 penilai yaitu manajemen rekayasa lalu lintas, seksi parkir, staff administrasi parkir. Permasalahan dalam penilaian kinerja terbaik petugas parkir adalah belum ada sistem yang terstruktur sehingga waktu penilaian cukup lama sekitar kurang lebih 2-3 minggu. Selain itu penilaian masih cenderung subjektif misalnya penilaian petugas parkir berdasarkan kedekatan dan kekeluargaan sehingga menyebabkan kecemburuan. Mengatasi hal tersebut diperlukan suatu sistem komputer yang membantu pengambilan keputusan yaitu sistem pendukung keputusan penentuan kinerja terbaik petugas parkir pada Dinas Perhubungan Kabupaten Asahan dalam penelitian ini menggunakan metode BORDA. Metode borda digunakan untuk menggabungkan hasil penilaian keputusan dari tiap penilai sehingga dapat memperoleh hasil akhir berupa kinerja terbaik petugas parkir. Tujuan dari penelitian ini adalah untuk membuat suatu sistem komputerisasi yang nantinya akan membantu dalam menentukan penilaian kinerja terbaik petugas parkir disetiap tahunnya. Berdasarkan hasil penelitian dari sistem penentuan kinerja terbaik petugas parkir berupa perangkingan dari nilai akhir setiap petugas parkir. Nilai tertinggi dijadikan sebagai saran kinerja terbaik petugas parkir. Kata kunci: metode borda; sistem pendukung keputusan; kinerja petugas parkir